BONUS DEMOGRAFI DI ERA ARTIFICIAL INTELLIGENCE: TANTANGAN GEOSTRATEGI INDONESIA - Endang Pujiati; Naelah Nur Salsabila; Salsabilla Maharani; Zeus Ardhan Arash; Isti Mar’atush Sholihah Budi Utami; Naura Jahraa Kusuma Putri; Suryo Ediyono (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Indonesia is currently navigating a crucial phase of its demographic bonus, where the surge in the productive-age population serves as a potential strategic asset for national development, provided it is managed effectively. However, this dynamic coincides with rapid disruptions from Artificial Intelligence (AI) and digitalization, which are restructuring the labor market through automation and shifting competence requirements. Without proactive measures to develop an adaptive workforce, this potential demographic advantage risks turning into a national vulnerability. This study aims to analyze the challenges of the demographic bonus and the transformation of the employment landscape driven by AI through the lens of Indonesia's geostrategy to reinforce national resilience. Utilizing a qualitative descriptive method with a literature review approach, this study finds that the emergence of AI acts as a double-edged sword: it offers high economic efficiency while simultaneously posing a risk of structural unemployment due to a widening skills gap. The findings indicate that optimizing the demographic bonus in the digital era demands integrative national policy reforms, including upgrading educational quality, accelerating digital literacy, and cultivating a resilient labor ecosystem to sustain national resilience.